Predicting Economic Activity in Serbia By Constructing Serbian Leading Economic Indicator (SERLEI) - Kamenković, Sandra S; Grubišić, Zoran (Industrija, 2013)
Timely identification of the next stage of the business cycle, or a shift in economic activity from the previous trend, is a critical factor for the success of counter-cyclical economic policy. This paper is based on the construction of a new leading indicator of the business cycle which, with a certain time lag, suggests the next stage of the business cycle in the Republic of Serbia. SERLEI (Serbian Leading Economic Indicator) is tested in the period of expansion and at the beginning of recession in the Serbian economy to show to what extent it was possible to predict a shift in business cycles